Employers of migrant women domestic workers from Albania and Ukraine - Kassimati, Koula (The Greek Review of Social Research, 2007)
<div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 344.538px; transform: rotate(0deg) scale(1.11574, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="425.0952">The views of employers of migrant women domestic workers from Albania and <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 362.912px; transform: rotate(0deg) scale(1.10935, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="424.88160000000005">Ukraine who are employed either to care for elderly people or to assist with the <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 381.285px; transform: rotate(0deg) scale(1.09861, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="424.06320000000005">domestic chores some days per month or week are focused on: how to locate the <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 399.658px; transform: rotate(0deg) scale(1.12553, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="424.3248000000001">workforce, the importance of the nationality of these domestic workers for the <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 418.031px; transform: rotate(0deg) scale(1.04237, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="424.2456000000001">employers, their work content and employment conditions, the relationship between <div style="font-size: 12.2681px; font-family: serif; left: 101.619px; top: 436.404px; transform: rotate(0deg) scale(1.11188, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_152_0" data-canvas-width="424.74">employers and employees and on the employers’ evaluation for the presence of migrants on the Greek labour market.